Body fat distribution, fat-free mass and cardiovascular function in the UK Biobank - Oguntade, AS; Lacey, B; Taylor, H; Lewington, S (BioMed Central, 2023)
Background We evaluated the independent associations of body composition measures on left ventricular ejection fraction (LVEF) and pulse wave arterial stiffness index (PWASI).